EFM - Elephant Flow Manager: uma arquitetura para detecção e tratamento de fluxos elefantes em DCNs - Rocha, André Luiz Beltrami (Universidade Federal de São Carlos, 2017)
One of the major issues in Data Center Networks (DCNs) is related to elephant flows. These flows typically are primarily responsible for network congestion, causing impacts on applications that are intolerant to delays. Although there are several works in the literature that analyze this type of traffic, none of them consider the impact of elephant flow size when perfoming the re-routing of them, influencing the Flow Completion Time (FCT) and throughput. In this way, this work presents EFM (Elephant Flow Manager) as a complete solution for monitoring and re-routing elephant flows in DCNs by observing the size of these flows in the network. The tests performed show that the size of the elephant flows influences the throughput and the FCT of the applications and, therefore, deserves to be observed. The evaluation of the solution was performed comparing the joint use of EFM with ECMP. In all tests, our re-routing solution was better when compared to pure routing with only ECMP. Then, this work presents three main contributions: (1) proposes and implements an architecture for the detection and treatment of elephant flows in DCNs (2) highlights the importance of the size of elephant flows in the re-routing of these in DCNs (3) the EFM in conjunction with the ECMP reduces the energy consumption in the DCNs, since the FCT of flows is reduced.
EFM - Elephant Flow Manager: an architecture for detection and treatment of elephant flows in DCNs
Keywords: Redes de Data Center; Fluxos Elefantes; Re-roteamento; Monitoramento; SDN; Openflow; Consumo de energia; Data center networks; Re-routing; Elephant Flows; Monitoring; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO